The Financial Performance Enhancement Through Entrepreneurial Orientation Moderation by Tri Hita Karana Culture - Ni Nyoman Yuni Juwitaristanty; Ni L P Wiagustini (Journal of Multidisciplinary Academic, 2021)
The purpose of this study aimed to investigate the moderating role of Tri Hita Karana (THK) culture on the effect of entrepreneurial orientation on financial performance. In this study, we obtain the population taken from all export-oriented handicraft industries in Bali, Indonesia. Here, the population criteria were proposed as a private industry that have a business license which is registered on Trade and Industry Department Bali Province to carry out business activities as a producers and exporters. Currently, there are 42 business units that meet the specified criteria. The data observation samples obtained from saturated sample with the owner or manager private industry. Here, the Partial Least Square technique was performed to analyse significant effect on financial performance. The result shows THK culture has a positive and significant effect on financial performance while THK culture is not proven to be able to moderate the relationship between entrepreneurial orientation and financial performance. In this study, the THK culture implies that the role of culture is not able to strengthen the relation of entrepreneurial orientation to financial performance. Moreover, the entrepreneurial orientation has a positive and significant effect on financial performance. This implies that higher the entrepreneurial orientation, the better the financial performance.